A ribosome-specialized translation initiation pathway is required for cap-dependent translation of vesicular stomatitis virus mRNAs - Lee, Amy Si-Ying (National Academy of Sciences, 2013)
Initiation is the primary target of translational control for all organisms. Regulation of eukaryotic translation is traditionally thought to occur through initiation factors and RNA structures. Here, we characterize a transcript-specific translation initiation mechanism that is mediated by the ribosome. By studying vesicular stomatitis virus (VSV), we identify the large ribosomal subunit protein rpL40 as requisite for VSV cap-dependent translation but not bulk cellular or internal ribosome entry site–driven translation. This requirement is conserved among members of the order Mononegavirales, including measles virus and rabies virus. Polysome analyses and in vitro reconstitution of initiation demonstrate that rpL40 is required for 80S formation on VSV mRNAs through a cis-regulatory element. Using deep sequencing, we further uncover a subset of cellular transcripts that are selectively sensitive to rpL40 depletion, suggesting VSV may have usurped an endogenous translation pathway. Together, these findings demonstrate that the ribosome acts as a translational regulator outside of its catalytic role during protein synthesis.